Editorial - Delfini C. de Oliveira, Ana Claudia; Delfini C. de Oliveira, Ana Claudia; Delfini C. de Oliveira, Ana Claudia (Corporación Universitaria Americana, 2019)
With great pleasure we present this issue of the journal Pensamiento Americano. Since 2008, PensamientoAmericano has contributed to the increase in scientific research, striving for the quality of discussionsdeveloped by renowned researchers in their respective areas. On this issue, it is not the exception. Inits twelfth volume, the journal set out topics that dialogue with the main contemporary dilemmas: environmentalissues, legal discussions, gender violence, new information technologies and labour conditions, education, armedconflicts, suicidal behaviors, intergenerational differences, globalization and alternative justice, artistic and culturalaspects are the issues that make up the analytical framework of this edition